Ethiopia adopts WLE research findings to improve the returns on its massive investments in soil and water management - CGIAR Research Program on Water, Land and Ecosystems (2017)
In 2017, the Prime Minister approved a policy to make all agricultural water technologies tax exempt. Ethiopia also adopted a new Soils Strategy to target soil fertility management interventions in various landscape niches; and the Sustainable Land Management Program (SLMP) began adopting new implementation interventions that target interventions at different landscape levels following community-led processes. These outcomes are a direct result of WLE research, capacity strengthening and policy engagement. Together, they can greatly enhance the impacts of agricultural investments.